Seismic Hazard Assessment and Land Use Analysis of Mangalore City, Karnataka, India. Issue 12 (15th October 2021) - Ramkrishnan, R; Kolathayar, Sreevalsa; Sitharam, T.G.
ABSTRACT: This article presents a combined seismic risk assessment of Mangalore city, considering seismic hazard and Land Use (LU) patterns. Probabilistic seismic hazard analysis was carried out considering different source models and attenuation relations to predict Peak Ground Acceleration at every square kilometer. LU of the area was assessed using GIS tools with the built-in supervised Gaussian maximum likelihood algorithm on processed remote sensing data from temporal Landsat images. The risk map showed the concentration of built-up area South-West, toward the sea and the seismic hazard following an increasing trend from the coast to further inland.